Bob Marley : the life of a musical legend - Jeffrey, Gary.; Riley, Terry (New York : Rosen Central, 2007)
Presents a brief profile of legendary songwriter and rhythm guitarist Bob Marley written in graphic comic format.
Who's who -- Trouble in paradise -- Rhythm and roots -- Bob Marley : the life of a musical legend -- Time will tell.
Includes bibliographical references (p. 47), discography, and index.
4.7
5-8
Keywords: Marley, Bob -- Comic books, strips, etc. -- Juvenile literature; Marley, Bob -- Cartoons and comics; Marley, Bob -- Comic books, strips, etc; Reggae musicians -- Jamaica -- Comic books, strips, etc. -- Juvenile literature; Blacks -- Cartoons and comics; Cartoons and comics; Musicians -- Cartoons and comics; Reggae music -- Cartoons and comics; Blacks -- Jamaica -- Comic books, strips, etc; Comic books, strips, etc; Musicians -- Jamaica -- Comic books, strips, etc; Reggae music -- Comic books, strips, etc